Creating Culture Organizational Citizenship Behavior and Performance Through Human Research Optimization - Edy Jumady, Syamsul Alam, Yana Fajriah, Muhammad I. N. Hamiddin, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2021)
We conducted this study to examine and explore the effect of developing human resources, competence, and motivation on Organizational Citizenship Behavior (OCB) and the Performance of State Civil Apparatus. This study uses a quantitative approach involving 320 respondents. Our research data was collected by distributing questionnaires directly to respondents. The results of this study indicate that the development of human resources has a positive and significant effect on Organizational Citizenship Behavior. Competence has a positive and significant effect on Organizational Citizenship Behavior. Positive and significant motivation on Organizational Citizenship Behavior. HR development has a positive and significant impact on the performance of ASN. Competence has a positive and insignificant effect on ASN performance. Positive motivation and not significant to the performance of ASN. Positive and significant motivation on the performance of ASN.